Pengaruh Implementasi Kebijakan KTP dan Kualitas Pelayanan terhadap Kepuasan Masyarakat - Gaib, Nurvia; Rachman, Ellys; Nggilu, Rukiah (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2024)
Government representatives become the target of criticism for the quality of public services. Based on the summary, it shows that there is a significant impact that caused by the influence of policy implementation and the influence of service quality on electronic KTP applicant satisfaction at the South Bolaang Mongondow Civil Registry office. This research uses a survey research type with a quantitative approach, with SPSS version 27.0 application analysis. Summary that we can conclude based on the result is that there is a significant influence of Policy Implementation (X1) on Community Satisfaction (Y) with a determinant value of 10.9%. The variable service quality (X2) on community satisfaction (Y) is 18.5%. (3) and the variable Electronic KTP Policy Implementation (X1) and Service Quality (X2) on community satisfaction (Y) has a determinant value of 24.8%.